Duplessis and the Union Nationale Administration - Seager, Allen (Labour / Le Travail, 1985)
This article reviews the book, "Duplessis and the Union Nationale Administration," by Richard Jones.
Keywords: DUPLESSIS & the Union Nationale Administration (Book); JONES, Richard; Nonfiction; POLITICAL development; REVIEWS; books